Gambaran Self-Esteem Siswa SMA dan Implikasinya dalam Pelayanan Konseling - Sandy, Fadillah; Nurfarhanah, Nurfarhanah (Lembaga Yasin AlSys, 2024)
This study is motivated by students who cannot express their opinions, cannot accept their strengths and weaknesses and have difficulty interacting with friends and the irenvironment, feel inferior to their body shape, different skin color compared to their friends and during class hours students do not dare to express their opinions in front of the class because they are not confident. This study aims to describe the description of self-esteem at SMAN 1 2X11 Enam Lingkung. This type of research is quantitative with a descriptive approach. The population of this study was 694 students at SMAN 1 2X11 Enam Lingkung in the 2024/2025 school year and a sample of 328 students taken through proportional random sampling technique. Data collection in this study used a Likert scale, namely a self-esteem questionnaire that has been tested for validity with the Pearson correlation formula (0.355). The data in this study were processed with descriptive statistical analysis techniques. The results of this study indicate that the self-esteem of students at SMAN 1 2X11 Enam Lingkung as a wholeis in themoderate category (65.24). Based on the results of this study, counseling teachers can provide assistance to improve students' self-esteem in the form of information services, content mastery services and group guidance services.